2015
DOI: 10.1007/s00592-015-0771-7
|View full text |Cite
|
Sign up to set email alerts
|

The advent of biosimilars for the treatment of diabetes: current status and future directions

Abstract: Biosimilar insulins are likely to enter the market of diabetes therapies as patents for major branded insulin products start to expire in the next few years (on June 2014, the European Medicines Agency authorized the first biosimilar of insulin glargine, Abasria, 100 Units/ml, for the treatment of diabetes mellitus). This would allow providing comparable clinical benefits of the current available insulins at a significantly lower cost, thus increasing the affordability and access of insulin treatment for patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
0
19
0
2
Order By: Relevance
“…In the past decades, the various treatments were used to prevent and treat the aforementioned MDs but they are still limited [29]. For diabetes, the long term treatment is insufficient for controlling blood glucose by daily medicines take like metformin or subcutaneous injection of insulin, as blood glucose is easy fluctuated by the intake of food and physical activity [30]. For the treatment of NAFLD, although lifestyle modification, vitamin E, and clinical surgery as main methods are commonly used, there is no effective medicine to prevent the pathological development of it [31].…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…In the past decades, the various treatments were used to prevent and treat the aforementioned MDs but they are still limited [29]. For diabetes, the long term treatment is insufficient for controlling blood glucose by daily medicines take like metformin or subcutaneous injection of insulin, as blood glucose is easy fluctuated by the intake of food and physical activity [30]. For the treatment of NAFLD, although lifestyle modification, vitamin E, and clinical surgery as main methods are commonly used, there is no effective medicine to prevent the pathological development of it [31].…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…Similar to chemical drugs, once the patent of a biological product is expired the marketing of biosimilars and generics is possible 79 . These patent expirations, combined with rising healthcare costs and population aging worldwide are paving the way for the development of biosimilars and biobetters, opening new commercial opportunities 80, 81.…”
Section: Global Consumer Market Of Microbial Biopharmaceuticalsmentioning
confidence: 99%
“…These patent expirations, combined with rising healthcare costs and population aging worldwide are paving the way for the development of biosimilars and biobetters, opening new commercial opportunities 80, 81. Many biosimilars are currently under development and these follow-on products will inevitably play substantial competition and an increasing role in healthcare in upcoming years 79, 82. In Brazil the scenario is modest, but considering the global panel and recent government incentive for the national biopharmaceutical industry development, we expect to see more patents in the near future and also novel opportunities for biosimilars and biobetters.…”
Section: Global Consumer Market Of Microbial Biopharmaceuticalsmentioning
confidence: 99%
“…Insulin products can elicit the formation of insulin antibodies, often without clinical consequences [8, 9]. However, rare instances exist where the presence of insulin antibodies may have clinically relevant effects on efficacy and safety [911].…”
Section: Introductionmentioning
confidence: 99%
“…However, rare instances exist where the presence of insulin antibodies may have clinically relevant effects on efficacy and safety [911]. We have previously shown that the immunogenicity profile of LY IGlar is similar to that of IGlar [7], and that both LY IGlar and IGlar have comparable insulin antibody response (IAR) profiles, with no observed effect on efficacy and safety outcomes [7].…”
Section: Introductionmentioning
confidence: 99%